Reduced Net CO2 Uptake During Dry Summers in a Boreal Shield Peatland. Issue 2 (11th February 2023) - McDonald, R. M.; Moore, P. A.; Helbig, M.; Waddington, J. M.
Abstract: Peatlands are globally important long‐term sinks of atmospheric carbon dioxide (CO2 ). However, there is concern that climate change‐mediated drying will reduce gross primary productivity (GPP) and increase ecosystem respiration (ER) making peatlands vulnerable to a weaker carbon sink function and potential net carbon loss. While large and deep peatlands are usually resilient to moderate summer drying, CO2 exchange in shallow Boreal Shield peatlands is likely more sensitive to drying given the reduced groundwater connectivity and water storage potential. To better understand the carbon cycling responses of Boreal Shield peatlands to meteorological conditions, we examined ecohydrological controls on CO2 fluxes using the eddy covariance technique at a shallow peatland during the summer season for 5 years, from 2016–2020. We found lower GPP in dry summer years. Mean summer water table depth (WTD) was found to be significantly correlated with summer total net ecosystem CO2 exchange ( R 2 = 0.78; p value = 0.046) and GPP ( R 2 = 0.83; p value = 0.03), where wet summers with a WT close to the peat surface sequestered more than twice the amount of CO2 than dry summers. Our findings suggest that shallow Boreal Shield peatland GPP may be sensitive to climate‐mediated drying as they may switch to a net CO2 source in the summer season when WTDs exceed a critical ecohydrological threshold for a prolonged period of time. Plain Language Summary: Peatlands take in carbon from the atmosphere and store it in the ground as peat, a process that helps to regulate climate change. Peatlands in the Boreal Shield are positioned in bedrock basins. Their water table (WT) is controlled by precipitation, which can trigger water flow over the bedrock between wetland ecosystems. Due to this unique setting, we expected Boreal Shield peatlands to be more sensitive to differences in growing season meteorological conditions from year to year. We used 5 years of carbon dioxide (CO2 ) exchange measurements between land and atmosphere during the summer season in a Boreal Shield peatland in Ontario, Canada. We found the peatland vegetation took up more CO2 from the atmosphere during summers with more rain which keeps the WT in the peatland closer to the peat surface. The peatland took up less CO2 when the summer was dry. Our findings provide insight into how Boreal Shield peatlands are responding to summer droughts under current climate conditions. Key Points: Summers with higher rainfall (and lower P‐PET) maintain a water table near the peat surface and have greater net carbon dioxide (CO2 ) uptake Interannual differences in summer net ecosystem CO2 exchange are attributable to changes in summer gross primary production Shallow Boreal Shield peatlands may switch to a net carbon source in the summer season